THE ROLE OF TRANSFORMATIONAL LEADERSHIP FOR TALENT RETENTION AND ENGAGEMENT - Sinha, Manish Kumar; Mukherjee, Kausik (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Transformational leadership plays a crucial role in fostering talent retention and employee engagement, both of which are vital for organizational success in today’s competitive landscape. This leadership style, characterized by qualities such as inspirational motivation, individualized consideration, idealized influence, and intellectual stimulation, inspires employees to align with organizational goals while fostering personal growth. Transformational leaders create an engaging work environment where employees feel valued, supported, and empowered, leading to increased job satisfaction and loyalty. By addressing the unique needs and aspirations of their team members, these leaders reduce turnover rates and enhance overall employee retention. This study explores how transformational leadership impacts key metrics such as job satisfaction, engagement levels, and collaboration effectiveness. Using both qualitative and quantitative methods, the research examines pre- and post-implementation data to highlight measurable improvements in retention and engagement. Show actionable insights, this study aims to guide leaders and HR professionals in creating strategies that leverage transformational leadership to build resilient, engaged, and high-performing teams.